Design and Flow Analysis of an Adjustable Check Valve by Means of CFD Method - Filo, Grzegorz; Lisowski, Edward; Rajda, Janusz (Energies (Basel), 2021)
The article presents results of research on an adjustable check valve. In particular, the article deals with improvement of flow characteristics and reduction in pressure losses of an existing valve design. The subject of the research was the valve body in the form of a steel block intended for mounting a typical cartridge valve insert. Two variants of the valve body were analysed: a standard one, which is currently in production, and the proposed new solution, in which the geometry was modified based on the results of CFD simulations. The main research task was to properly shape and arrange holes and flow channels inside the body, between the cartridge valve and the connecting plate. Using CFD analyses, a solution for minimising the flow resistance was sought and then the method of modifying flow channels geometry was developed. The CFD simulation results showed a significant reduction in pressure loss, up to 40%. The obtained simulation results were verified on a test bench using a prototype of the proposed valve block. A high degree of consistency in the results of CFD simulations and laboratory experiments was achieved. The relative difference between simulation and experimental results in the entire considered range of the flow rate did not exceed 6.0%.